(3VeGfGJ Mbhb GdEfSGf ai eQMdI GdJMbjb GdGHJOGFi (B/ s - (3ceGd GdOjf eUWai Jhajb TYjH s; (3ahRjI YHOGdSJGQ s; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2011)
(3JJfGhd gPg GdOQGSI (B" (3VeGfGJ Mbhb GdEfSGf ai eQMdI GdJMbjb GdGHJOGFi (B" (3Ef Mbhb GdEfSGf ai eUQ JYQVJ hdG RGdJ JJYQV dNWQ Mbjbi ai eQMdI GdJMbjb GdGHJOGFi aYdi GdQZe ef Cf bGfhf GdELQGAGJ GdLfGFjI GdeUQi GdMGdi bO UOQ eJVefG VeGfGJ LeI ddeJgejf EdG Cf GdeTQY GdeUQi CHi Pdc hXd jfJbU JHGYG ef gPg GdVeGfGJ aHebJVi GdbGfhf Qbe (B353 (3dSfI (B1952 (3SdH GdeTQY GdJMbjb ef GdbGVi hYgO Hg Edi GdfjGHI GdYGeI hHebJVi GdbGfhf Qbe (B170 (3dSfI (B1981 (3bGe GdeTQY HEdZGA fXGe eSJTGQ GdEMGdIs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFi, (B2011s
(3jTJed Ydj EQLGYGJ HdjhLQGajI(B: (3UaMI (B625-667s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3GdJMbjb GdGHJOGFi s; (3Mbhb GdEfSGf s; (3VeGfGJ s; (3GdfjGHI GdYGeIs; (3GdTQYjI GdELQGFjI s; (3GdMHS GdGMJjGWjs; (3VHW GdeQGSdGJs; (3GdGSJLhGHs; (3Mb GdeJge aj GdUeJs; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs